Entre o efêmero e o perene: constituição, circulação e relações imagéticos-discursivas d(n)as tiras de Armandinho - Anderson Jose de Paula (2024)
This research has as its object of study the Armandinho strips, by Alexandre Beck, whose character has become very expressive on social networks. The general objective is to problematize, through the imagetic-discursive bias, the political-racial-pandemic representation and the effects of meaning proposed by Armandinho's strips in the interactional process that occurred on his homonymous fanpage on the social network Facebook. Specifically, this research is interested in: a) tracking the constitutive process of the verbal-visual text through the conditions of production of Armandinho's strips, based on the assumptions of French-oriented Discourse Analysis, hereinafter ADF, in interface with Comics Studies; b) investigating the representations and the imagetic-discursive effects of meaning; c) approaching Armandinho's strips to the notions of imagetic-discursive chronicle and irony through the discursive-deconstructivist bias; and d) verifying the meanings of ephemeral and perennial in the discursive excerpts of the analytical gesture. Thus, the hypothesis was that Armandinho’s strips, through a (not at all) light and (not at all) objective language, deal with controversial and complex themes and introduce political and social dissent, in an ephemeral and perennial way, with/through humor and in an ironic manner, bringing the strips closer to the imagetic-discursive chronicle. I therefore formulate three research questions: 1) Regarding the imagetic-discursive perspective, the constitution of Armandinho’s strips mobilizes what types of political and social representation and what effects of meaning? 2) How does the constitutive process of the verbal-visual text bring the strips closer to the notions of the imagetic-discursive chronicle and irony from the perspective of the discursive-deconstructivist theory? 3) In what way do the meanings of ephemeral and perennial permeate the excerpts present in the analytical gesture? To this end, in the (trans)disciplinary theoretical foundation undertaken here, the following stand out: ADF (Pêcheux, 1997, 1997a, 1999, 2008), (Pêcheux and Fuchs, 1997), (Foucault, 1979, 1985, 1996, 1999, 2008), (Orlandi, 2001, 2002, 2009, 2012, 2014), the discursive-deconstructivist perspective (Coracini, 2007, 2010) and (Derrida, 2001, 2001a), the imagistic-discursive notions through comics studies (Cirne, 2000), (Chinen, 2011), (Postema, 2018) and (Vergueiro, 2012), specifically, the strips (Ramos, 2010, 2017) and language and semiotics (Cagnin, 1975, 2014). The methodology echoes Foucault's thought (1979, 1999, 2008) through archeogenealogy that allows me to excavate the linguistic and image-discursive materiality in search of the production of other meanings. Armandinho's strips constitute this writing from the summary, since the corpus of this research is composed of 181 strips, published between March and September 2020. However, for the analytical-interpretative gesture, I cast two axes, in two excerpts: R1M1 – Pandemic; R1M2 – Political-Racial and R2 – Political-Pandemic, in groups of two, three and six strips, respectively, published between March and September 2020, within the COVID-19 Pandemic archive, which constitute the corpus of analysis. Since there is a volume of strips, they were constituting the thesis and were organized into groups and colors: cross-reference strips (yellow), interactive strips (pink), sequence (green) and clipping (blue). Therefore, the thesis is divided into three parts. In the first part, I present in Chapter 01 the place of strips in comics studies and the conditions of production of the constitution of Armandinho's strips; in Chapter 02 I characterize the character Armandinho and his author Alexandre Beck. In the second part, I refer to Chapter 03 and present the theoretical foundation based on the ADF in order to promote reading gestures and mobilize effects of meaning. In the other Chapter of this part, the fourth, I raise the theoretical assumptions found in the chosen framework, in addition to the (trans)disciplinary threads. I also mobilize the methodological path based on Foucaultian archeogenealogy. In the third part, fifth chapter, I present the analytical path in which the analyzed excerpts made it possible to see a child crossed by other discourses in order to recognize, point out, reflect and/or denounce the political-pandemic-racial problems and point to a media discourse that functions as a reaction, sometimes perennial, sometimes ephemeral, to the socio-historical-political-cultural-ideological context in force at the time in which the strips are produced and published. Furthermore, due to this reaction, they approach the image-discursive chronicle and, having humor as a disjunctive element, they also approach irony from the discursive-deconstructivist perspective. Keywords: Discourse, Verb-Visual Language, Strips, Representation